ChemInform Abstract: Carbamidocyclophanes F and G with anti‐Mycobacterium tuberculosis Activity from the Cultured Freshwater Cyanobacterium Nostoc sp. Issue 26 (1st July 2014) - Luo, Shangwen; Kang, Hahk‐Soo; Krunic, Aleksej; Chlipala, George E.; Cai, Geping; Chen, Wei‐Lun; Franzblau, Scott G.; Swanson, Steven M.; Orjala, Jimmy
Abstract Carbamidocyclophane F (Ia) shows a potent anti‐Mycobacterium tuberculosis activity in the microplate Alamar blue assay and low‐oxygen‐recovery assay with MIC values of 0.8 and 5.4 μM, respectively.